Development and validation of a new non-disease-specific survey tool to assess self-reported adherence to medication - Larsen, Rønnaug Eline; Pripp, Are Hugo; Krogstad, Tonje; Johannessen Landmark, Cecilie; Holm, Lene Berge (Frontiers in Pharmacology, 2022)
Background Patients’ non-adherence to medication affects both patients themselves and health care systems. Consequences include higher mortality, worsening of disease, patient injuries, and increased health care costs. Many existing survey tools for assessing adherence are linked to specific diseases and assessing medication-taking behavior or identifying barriers or beliefs. This study aimed to develop and validate a new non-disease-specific survey-tool to assess self-reported medication-taking behavior, barriers, and beliefs in order to quantify causes of non-adherence and to measure adherence. Methods The survey tool was developed after literature-searches and pilot-testing. Validation was conducted assessing the psychometric properties of content, construct, reliability, and feasibility. Content validity was assessed by subject-matter-experts and construct validity by performing exploratory factor analysis. Reliability assessment was done by calculating internal consistency, Cronbach’s alpha and test/retest reliability, Intraclass-Correlation-Coefficient (ICC) in addition to Standard Error of Measurement (SEm). A Receiver-Operating-Characteristic (ROC) curve and Lui method was used to calculate the statistical cut-off score for good versus poor adherence. Survey responses from Norwegian medication users over 18 years recruited via social media were used for the factor analysis and Cronbach’s alpha. Results The final survey-tool contains of 37 causes of non-adherence connected to medication taking behavior and barriers to adherence and beliefs associated with adherence. . The overall result for all 37 items demonstrated reliable internal consistency, Cronbach’s alpha=0.91. The factor analysis identified ten latent variables for 29 of the items, explaining 61.7% of the variance. Seven of the latent variables showed reliable internal consistency, Medication fear and lack of effect, Conditional practical issues, Pregnancy/breastfeeding, Information issues, Needlessness, Lifestyle, and Avoiding stigmatization (Cronbach’s alpha=0.72-0.86). Shortage showed low internal consistency (Cronbach’s alpha=0.59). Impact issues and Personal practical issues showed poor internal consistency (Cronbach’s alpha=0.51 and 0.48, respectively). The test/retest reliability ICC=0.89 and SEm=1.11, indicating good reliability. The statistical cut-off score for good versus poor adherence was 10 but the clinical cut-off score was found to be 2. Conclusions This survey tool demonstrated to be a valid and reliable instrument for assessing adherence. Further studies will examine the ability of the tool for measuring adherence enhancing effect following interventions.